Tau phosphorylation and PAD exposure in regulation of axonal growth - Morris, S. L.; Brady, S. T. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Tau is a microtubule associated phosphoprotein found principally in neurons. Prevailing dogma continues to define microtubule stabilization as the major function of tau in vivo, despite several lines of evidence suggesting this is not the case. Most importantly, tau null mice have deficits in axonal outgrowth and neuronal migration while still possessing an extensive microtubule network. Instead, mounting evidence suggests that tau may have a major function in the regulation of fast axonal transport (FAT) through activation of neuronal signaling pathways. Previous studies identified a phosphatase activating domain (PAD) at the tau N-terminal that is normally sequestered, but is constitutively exposed in tauopathies. When exposed, the PAD activates a signaling cascade involving PP1 and GSK3β which affects cellular functions including release of cargo from kinesin. Furthermore, we discovered that PAD exposure can be regulated by a single phosphorylation at T205. Exposure of the PAD is an early event in multiple tauopathies and a major contributing factor to neurodegeneration associated with tau hyperphosphorylation. However, effects of tau PAD exposure on anterograde FAT raised the interesting possibility that this pathway may be a mechanism for physiological regulation of cargo delivery through site-specific phosphorylation of tau and transient activation of PP1 and GSK3β. Significantly, there is already evidence of local control of PP1 and GSK3β at sites which require cargo delivery. Methods: To investigate this hypothesis, first we evaluated cellular localization of tau PAD exposure, pT205 tau phosphorylation, and active GSK3β in primary hippocampal neurons during development. Second, we analyzed the axonal outgrowth of tau knockout neurons following transfection with full length hTau40-WT, hTau40-ΔPAD, or hTau40-T205A. Results and Discussion: The results presented here suggest that transient activation of a PP1-GSK3β signaling pathway through locally regulated PAD exposure is a mechanism for cargo delivery, and thereby important for neurite outgrowth of developing neurons.